Effect of Paclobutrazol on Growth and Development of Curcuma alismatifolia Gagnep. Grown Off-season - Boontiang, Kriangsuk; Chutichudet, Benjawan; Chutichudet, Prasit (Naresuan University Journal: Science and Technology (NUJST), 2019)
A study on the effects of paclobutrazol on growth and development of C. alismatifolia Gagnep. grown in the off-season was conducted on an open field. A comparison was done between plants grown under sunlight plus 2 hrs. extra night light without paclobutrazol (Control 1) and plants grown under sunlight source without paclobutrazol (Control 2). This experiment was done by a completely randomized design with 6 treatments and 10 replications (10 plants/ replication). The results demonstrated that plants grown with paclobutrazol treatments were significantly affected in both height and peduncle length. The 600 mg/L paclobutrazol treatment was non-significant difference in terms of leaf area, chlorophyll content in leaf, non-structural carbohydrate content in rhizome, pseudo-stem, peduncle and inflorescence, and anthocyanin content in coma bract compared to control 1. Earliest flowering parameters; the day to inflorescence apparent (day 47.2) and first flower opening (day 47.2) were found in plants grown under sunlight + 2 hours night-break without paclobutrazol. The most delay inflorescence apparent (day 62.9) and first flower opening (day 94.1) were recorded under sunlight source without paclobutrazol. Keywords: off-season Curcuma alismatiflolia Gagnep., paclobutrazol, vegetative growth, physical development, chemical compound